Stable Isotope Ratio Analysis for the Comparison of Timber From Two Forest Concessions in Gabon - Watkinson, Charles J.; Rees, Gareth O.; Gwenael, Moundounga Cynel; Gasson, Peter; Hofem, Sabine; Michely, Lina; Boner, Markus (Frontiers in Forests and Global Change, 2022)
Consumers are becoming increasingly aware of the environmental impacts caused by deforestation and illegal logging and there is an increasing demand for supply chain transparency and traceability of wood products. Many importing and exporting nations have implemented regulations which aim to control the origin and species of traded timbers of high ecological importance and economic value. However, despite growing interest in method development for timber authentication purposes, many studies have been limited by insufficient numbers of authentic timber reference samples. Our aim was to address the differences in stable isotope ratio profile of bulk, homogenised wood samples collected from living or recently felled trees in two FSC concessions in Gabon, which are approximately 240km apart, for the purposes of origin classification and protecting valuable forest commodities. Forty-seven timber samples comprising ten genera of tropical trees were obtained using a Pickering Punch sampling device or chainsaw from two forest concessions in Gabon (Precious Woods Group and Compagnie des Bois du Gabon) during July 2019. Samples were subject to 𝛿18O, 𝛿2H, 𝛿13C, 𝛿15N and 𝛿34S stable isotope analysis using elemental analysis-isotope ratio mass spectrometry (EA-IRMS). Results show that significant differences are evident in the stable isotope ratios of Aucoumea klaineana between Precious Woods Group and Compagnie des Bois du Gabon forest concessions. Relationships are evident between climatic and geological variables and the stable isotope ratios of the samples suggesting that further degrees of origin classification may be achievable in Gabon. For other species, insufficient numbers meant the possibility to determine discriminating factors between the two concessions was limited though data from these samples may prove useful to contribute to the understanding of stable isotope variability in tropical timber. The data presented establish a basis for evaluating origin claims of forest products and timber from the Compagnie des Bois du Gabon and Precious Woods Group concessions and lay a foundation for development of timber tracking technologies in Gabon. The technique can be used for purposes of due diligence or forensic investigation by law enforcement as part of demand-side regulations such as the EU Timber Regulation, Illegal Logging Prevention Act, or the Lacey Act.